Thermodynamic properties of naphthoxazole and naphthothiazole derivatives: Experimental and computational studies. (December 2018) - Silva, Ana L.R.; Morais, Victor M.F.; Ribeiro da Silva, Maria D.M.C.
Graphical abstract: Highlights: Combustion enthalpies for two naphthoxazoles and one naphthothiazole have been determined by combustion calorimetry. Enthalpies of sublimation/vaporization of three naphthoazole derivatives have been measured by Calvet Microcalorimetry. Vapour pressure vs temperature of 2-methylnaphtho[2, 3- d ]oxazole and 2-methylnaphtho[1, 2- d ]thiazole by Knudsen effusion. Gas-phase enthalpies of formation for four naphthoxazoles/naphthothiazoles were estimated from computational approach. Abstract: The energetic study of 2-methylnaphtho[1, 2- d ]oxazole (MN12O ), 2-methylnaphtho-[2, 3- d ]oxazole (MN23O ) and 2-methylnaphtho[1, 2- d ]thiazole (MN12T ) has been performed experimental and computationally. The enthalpies of combustion and sublimation/vaporization of these compounds were determined, respectively, from static or rotating bomb combustion calorimetry and high temperature Calvet microcalorimetry and/or the Knudsen-effusion studies. These experimental data allow derivation of the corresponding gas-phase standard molar enthalpies of formation of the three compounds. Additionally, we have obtained the gas-phase standard molar enthalpies of formation of these three compounds, as well of the 2-methylnaphtho[2, 3- d ]thiazole (MN23T ), through high level ab initio calculations, at the G3(MP2)//B3LYP and DLPNO-CCSD(T)/cc-pVTZ levels of theory. The computational study of the molecular structures of the compounds has been carried out. Furthermore, a relationship between the energetic and structural characteristics of these molecules was also evaluated.